Evaluasi Ukuran dan Bentuk Biji Genotip-genotip Mutan Kedelai Generasi M4 - Elfan Waisimon; Noladhi Wicaksana; Anas Anas; Meddy Rachmadi (Zuriat, 2019)
Soybean was one of the most important crop plants in Indonesia, but the need has not been fulfilled yet because its productivity was low. This study aims to obtain genotypes of M4 soybean mutant generation based on phenotypic characters of seed size and seed shape. The experiment was carried out in the experimental methods without spatial design, used 19 soybean mutant genotypes on M4 generation and Arjasari variety as a control. Eight characters of seed size (seed length, seed thickness, seed width, seed dimension, and 100 seed weight) and seed shape (seed length–thickness ratio, seed length-width ratio, and seed thickness–width ratio) have observed. Data analyzed with F-test, z-test, cluster analysis, and correlation analysis. The results showed that the seed size and seed shape characters had narrow intrapopulation variations. Eight genotypes of soybean mutants, namely MRAR 14-11-17-5, MRAR 15-17-31-11, MRAR 26-6-21-8, MRAR 29-12-26-11, MRAR 29-15-33 -7, MRAR 29-15-36-4, MRAR 29-15-36-8, and MRAR 29-15-30-10, have more significant seed size characters compared to Arjasari varieties. The MRAR genotypes 15-17-31-11 and MRAR 29-12-27-8 have a more rounded seed shape than the Arjasari variety. The seed size and seed shape characters correlated very strongly with each other. Seed size characters do not associate with seed shape characters.